Análise do desempenho, estabilidade e confiabilidade de estações de tratamento de esgoto no Ceará e proposta de uso de microalgas para a melhoria da qualidade de seus efluentes - Lobão, José Reges da Silva (2014)
In the present research was an elaborate investigative methodology inherent in effluent from sewage treatment plants in the State of Ceará. For this study were considered patterns BOD (biochemical oxygen demand), COD (chemical oxygen demand), TSS (Total suspended solids), CF (faecal coliforms), temperature, Nitrogen Compounds (Ammonia, phosphorus, nitrate) and pH, as the most representative parameters, as usual in the monitoring of ETE's, as the levels established by CONAMA (National Environment Council) and by State laws SEMACE (supervision of the Environment of the State of Ceará). The main objective is to elaborate a methodology research to quality of sewage treatment, as well as analyze the variability of the effluent samples, reliability, stability, sort the waste stations as Pollution program standards of Hydrographic Basins (PRODES) and analyze the impact of effluent polishing using microalgae like Spirulina platensis. The methodology was the approach and experimentation, qualitative and quantitative information, including evaluation of the efficiency, reliability and stability, which contributed to the rapprochement of systematic project with changes of variables concerning ETE ' s. The evaluation showed that the standards ETEs studied reached irregular performances, considering the standards of efficiency and strict confidence levels. Also, it was verified that the default maximum hit from Ceará Stations turned out to be the level F, considered median level. It was noted further that the polishing with microalgae promoted a reduction of 51.5%, 39.4% and 38.7% of the load of cod, BOD and TSS, respectively, with respect to the conventionally treated sewage effluent